2016
DOI: 10.1007/s12070-016-0973-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study to Evaluate the Association Between Sensorineural Hearing Loss and Diabetes Mellitus in Poorly Controlled Patients Whose HbA1c >8

Abstract: The relationship between sensorineural hearing loss (SNHL) and Diabetes mellitus has been known since more than 150 years. The pathophysiology of diabetes related hearing loss is speculative. Hearing loss is usually, bilateral, gradual onset, affecting higher frequencies. This study aims at knowing the prevalence of SNHL in DM and its relation to age, sex, duration of DM and control of DM. A total of 50 type 2 diabetics of age group 30-65 years were involved in the study. FBS, PPBS, HbA1c of all the subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 12 publications
5
24
2
4
Order By: Relevance
“…1 Another study showed prevalence rate of 66%. 2 Diabetes and sensorineural hearing loss among non-elderly people was 45%. 3 Diabetes is usually classified as being of type 1 & type-2.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Another study showed prevalence rate of 66%. 2 Diabetes and sensorineural hearing loss among non-elderly people was 45%. 3 Diabetes is usually classified as being of type 1 & type-2.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic neuropathies affect peripheral sensation & various autonomic functions. 2,4 The pathological changes that accompany diabetes may similarly cause injury to the vasculature or the neural system of the inner ear. So the pathogenic effects of diabetes on the ear can be grouped into neuropathic, angiopathic and a combination of the two.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observation has been made by many other studies. 10,11 The occurrence of SNHL correlated with the levels of HbA1c among diabetics suggesting a possible significant association between diabetes and increased hearing loss as compared to the observation made by Kim MB et al in which they found that the risk of hearing loss increased progressively with increasing HbA1c levels above 5%. 10 5 individuals among cases had well controlled HbA1c (<5.6%), among whom only 1 had SNHL.…”
Section: Discussionmentioning
confidence: 74%
“…DM is one of the most common metabolic disorders, which is associated with hearing impairment [ 12 , 13 ]. Previous studies demonstrated that poorly controlled diabetics have significant hearing loss in high frequencies as compared with well controlled diabetes [ 12 , 14 , 15 ]. There is still a deal of controversy but, angiopathy and neuropathy have been considered important factors for the vestibular-cochlear disorders found in diabetic patients [ 16 ].…”
Section: Discussionmentioning
confidence: 99%